Estimation of protozoal diversity among stray cats in Malaysia - MARWA HASAN ABDULWAHAB; HASSANAIN AL-TALIB (Society for Indonesian Biodiversity, 2024)
Abstract. Abdulwahab MH, Al-Talib H. 2024. Estimation of protozoal diversity among stray cats in Malaysia. Biodiversitas 25: 2115-2120. This cross sectional study was carried out to estimate the current prevalence and protozoa species in stray cats feces in Malaysia. A total of 320 fresh fecal samples were collected from S.I Home Shelter-Selangor, EJ CAT Home- Melaka, and KB-Cat Shelter - Kelantan in Malaysia. The collected fecal samples were concentrated for the presence of intestinal protozoa using a ready-made commercial Parasep tube floatation method. The fecal samples were stained with iodine and examined for protozoa by microscopic examination. The overall prevalence of intestinal protozoa in cat feces was 73.1% (n = 234). Isospora felis was most frequently detected (n = 145; 62%), followed by Toxoplasma gondii (n = 75; 32%), Giardia intestinalis (n = 9; 3.8%), Entamoeba histolytica (n = 9; 3.8%), and Tritrichomonas foetus (n = 6; 12.5%). Monoparasitism was detected in 65.8%, which was more frequent than polyparasitism (34.2%). Therefore, the local population is at risk of exposure to a wide range of zoonotic protozoa through environmental contamination with cat feces, and the current findings should be used to mitigate public health risks. Prevention and control measures need to be taken to reduce prevalence rates, especially in socioeconomically disadvantaged communities where animals live in close proximity to humans, where poor sanitation and overcrowding exist along with a lack of veterinary care and awareness of zoonotic diseases.